The Types of Braconidae and Ichneumonidae (Hymenoptera: Ichneumonoidea) in the Museo de La Plata, Argentina - Aquino, Daniel Alejandro (2010)
The 154 type specimens of Braconidae and Ichneumonidae housed in the collection of División Entomología, Museo de La Plata, were examined and listed, providing update information on synonymies, valid names, categories of types, data of collection and hosts. The types belong to 42 species described by Blanchard (3), Dasch (1), De Santis (14), De Santis & Millán (1), De Santis & Redolfi (1), Fischer (2), Kula & Martínez (1), Mason (3), Millán & De Santis (1), Monetti (1), Porter (7), Townes (2), Townes & Gupta (1) and Townes & Townes (4). Two new combinations are proposed: Catolestes desantisi is transferred to Heterospilus desantisi (Monetti) comb. nov. and Opidnus sublaevis sublaevis to Oresbius sublaevis (Townes & Gupta) comb. nov. respectively.